Study Of Malaysian Rare Earth Elements: Mineral Characterization Of Monazite And Xenotime Concentrate From Amang - Nazatul Dzahir, Nurul Fatin Nazira (Universiti Sains Malaysia, 2022)
Amang, widely recognized for mineral tailings in Malaysia, is a cassiterite-tailing or tin oxide (SnO₂) secondary product inevitably formed from mineral separation processes such as gravitational, magnetic, and high-tensional separators. In Malaysia, rare-earth elements (REEs) bearing monazite and xenotime are recovered from amang. This paper aims to mineralogically characterize the monazite and xenotime concentrate from Malaysian amang. The optical microscope, and scanning electron microscope (SEM) equipped with an energy-dispersive X-ray (EDX) were used for ore morphology and mineral association assessment as well as mineral liberation analysis. X-ray fluorescence (XRF) and X-ray diffraction (XRD) were used to determine the monazite and xenotime concentrate sample composition and to identify mineral phases, respectively. XRF analysis confirmed that the dominant elements present in the sample monazite concentrate are P and Ce, followed by elements present in trace levels like La, Nd and Th. The xenotime concentrate, which indicated high amounts of Y and P, and also contained significant amounts of LREE and HREE. Phase analysis by XRD meanwhile revealed monazite-(Ce) and xenotime- (Y) as the major components in the monazite and xenotime representative group, respectively. Additionally, mineralogical analyses of polished sections were carried out and analysed under microscope and SEM/EDX. SEM images revealed the crystal structures of the monazite and xenotime concentrate samples are dominantly prismatic or can be seen as wedge-shaped crystals and dipyramidal, respectively. The findings demonstrated that the morphology, chemical composition and phase constituents of monazite and xenotime were conclusively identified.